2018
DOI: 10.1093/jmt/thy012
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Music Therapy Practice and Skill-Sharing in Dementia Care

Abstract: Public interest in the benefits of music for people with dementia has rapidly increased in recent years. In addition to clinical work with clients, music therapists are often required to support and train staff, families, and volunteers and skill-share some music therapeutic skills. Six music therapy researchers from six countries agreed it was timely to organize a roundtable and share their indirect music therapy practice and examples of skill-sharing in dementia care. This article was developed following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 25 publications
3
56
0
Order By: Relevance
“…However, this study has also revealed that participants experience that yoik is not being prioritised or systematically applied in in-care settings, despite the positive potential the participants have observed. Applying music-based activities in a sustainable way is generally acknowledged as a challenge (McDermott et al, 2018), and in the case of yoik, even more so. In in-care settings, yoik still lives on the margins, although the yoiking participants in this study experienced that in-care use of yoik could enhance wellbeing if applied in daily life situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study has also revealed that participants experience that yoik is not being prioritised or systematically applied in in-care settings, despite the positive potential the participants have observed. Applying music-based activities in a sustainable way is generally acknowledged as a challenge (McDermott et al, 2018), and in the case of yoik, even more so. In in-care settings, yoik still lives on the margins, although the yoiking participants in this study experienced that in-care use of yoik could enhance wellbeing if applied in daily life situations.…”
Section: Discussionmentioning
confidence: 99%
“…McDermott and colleagues suggest that music familiar to and preferred by the person with dementia connects him/her to his/her identity and sense of self, as music is closely linked to personal life events, life story and the individual personality (McDermott, Orrell & Ridder, 2014). Successful interventions in dementia care based on the use of familiar music have led to a countrywide implementation in Norway under the concept "Musikkbasert Miljøbehandling" (MMB) or Music-based environmental treatment (Myskja, 2012; Nasjonalt kompetansesenter for kultur, helse & omsorg), and within the international community of music and health professionals, similar measures are being investigated and implemented (McDermott et al, 2018;Ridder, Stige, Qvale & Gold, 2013).…”
Section: Yoik Revival and Other Decolonisation Measuresmentioning
confidence: 99%
“…Baker and Yeates (2018) developed a therapeutic group songwriting intervention for family carers, which was designed to support their caring role; their qualitative findings showed that carers valued the shared group process and the opportunity to take time away from their caring responsibilities to reflect on their experiences. McDermott et al (2018) highlight the potential for optimising the benefits of music therapy through ‘indirect music therapy practice’, giving examples of various approaches where Music Therapists share skills and offer training to paid and unpaid caregivers in order to improve quality of daily care through the use of music.…”
Section: Introductionmentioning
confidence: 99%
“…Depression symptoms in dementia is an ongoing issue as elderly are transitioning to nursing homes and experiencing cognitive decline ( 13 ). Although research has shown that many music therapists have developed techniques that may be easily duplicated by care staff to address symptoms in dementia ( 14 , 15 ), and nursing research has demonstrated positive effects of music incorporated during caregiving ( 10 , 16 ), few studies show how collaborative efforts between music therapy and nursing may help to maintain reduction of depression symptoms. For this study, we measure the effectiveness of a 2-weeks music therapy intervention followed by a music activity facilitated by certified nursing assistants (CNAs) trained to incorporate singing and music-with-movement into their caregiving activities.…”
Section: Introductionmentioning
confidence: 99%